1999
DOI: 10.1088/0957-4484/10/3/304
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional manipulation of carbon nanotubes under a scanning electron microscope

Abstract: Carbon nanotubes are manipulated in three dimensions inside a scanning electron microscope (SEM). A custom piezoelectric vacuum manipulator achieves positional resolutions comparable to scanning probe microscopes, with the ability to manipulate objects along one rotational and three linear degrees of freedom. This prototypical device can probe, select and handle nanometre-scale objects such as carbon nanotubes in order to explore and correlate their mechanical and electrical properties. Under real-time SEM ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
125
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(132 citation statements)
references
References 22 publications
4
125
0
3
Order By: Relevance
“…Many experimental [4][5][6][7][8] and theoretical [9][10][11][12][13][14] studies have been performed on single-and multi-walled carbon nanotubes. In particular, deformation modes and nanotube stiffnesses have been closely examined.…”
Section: Wall Thicknessmentioning
confidence: 99%
“…Many experimental [4][5][6][7][8] and theoretical [9][10][11][12][13][14] studies have been performed on single-and multi-walled carbon nanotubes. In particular, deformation modes and nanotube stiffnesses have been closely examined.…”
Section: Wall Thicknessmentioning
confidence: 99%
“…Depending on the intended application, one wants to be able to pattern SWNTs as individual tubes (3,4), small bundles (5), or thin films (6,8,9). Previous studies have shown that individual carbon nanotubes can be positioned (10), bent (11), and even welded (12) with nanometer accuracy by using scanning probe instruments. This level of manipulation is limited to serial and therefore slow processes that span relatively short distances (100 m).…”
mentioning
confidence: 99%
“…The SEM captured images of the wires in different resonant modes, and the frequencies were used to calculate the bending modulus of the nanowires which was found to be about 47 GPa instead of 72 GPa which is the accepted value for bulk fused silica fibers. Yu et al have designed an implemented a nanomanipulator system that fits inside an SEM [6,7]. Much like the work of Dikin et al, the nanomanipulator setup was used to excite nanowires at resonant frequencies [6].…”
Section: Galfenol Nanowire Acoustic Sensorsmentioning
confidence: 99%
“…Much like the work of Dikin et al, the nanomanipulator setup was used to excite nanowires at resonant frequencies [6]. The setup has also been used for examining carbon nanotubes [7]. Under the inspection of an SEM, the nanotubes were picked up and fixed to AFM cantilevers where they could be manipulated and bent while measuring properties such as stiffness and conductivity.…”
Section: Galfenol Nanowire Acoustic Sensorsmentioning
confidence: 99%
See 1 more Smart Citation